Evaluation techniques used by teachers in elementary home economics a pilot study - Bunagan, Cellie Templo; Lavides, Violeta C. (1971.)
A pilot study on evaluation techniques in elementary home economics was conducted in three school districts in Quezon City with 40 teachers as subjects. Use and practicability of 25 techniques in different areas of home economics, problems met in their use, and suggested solutions were asked of the respondents. It was evident that 90-100% of the respondents used the following seven tests: unit tests, score card, observation, periodic test, self-rating scales, performance test and objective tests. The rest were employed to a lesser degree. The most-used achievement test was the daily quiz and among the objective tests, multiple choice, matching and completion types and identification types were used by 93%, 85%, and 80%, respectively. Use of the others varied from 55 to 73%. In almost all areas of home economics, performance and self-rating scales were found practicable. It appears from the above results that the appraisal of knowledge and understanding of concepts was the focus of evaluation of the teachers. Measurement of attitudes and appreciation was not given as much attention. Problems were mostly economic in nature and suggestions reflected an honest sincere desire on the part of the teachers to improve instruction and increase rapport with the community. Solution to problems therefore, was a joint undertaking of school administrators, teachers, parents and pupils. Recommendations on the more effective use of evaluation techniques are given. Also, topics for are given. Also, topics for future studies are indicated.
An abstract of a pilot study conducted for H.E. Education 291 - Seminar in Home Economics.
Keywords: Students -- Rating of -- Philippines; Home Economics -- Study and teaching -- Philippines